Application Of Pr ainisavira4@gmail.comoviding Green Bean Extract For The Production And Expenditure Of Breastmilk Of Postpartum Mother In Restu Bunda Independent Midwifery Clinic At Sempor, Kebumen - Indrayani, Eni; Saridewi, Adinda Putri; Istikomah, Nurul (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
Breastmilk is milk coming out of a mother after giving birth. It is not just as food,but also as liquid consisting of living cells, such as white blood cells, antibodies, hormones,growth factors, enzymes, and substances that can kill bacteria and viruses. The low coverage ofexclusive breastfeeding for infants under the age of six months is caused by the production ofbreastmilk which is hampered in the first days after delivery. Consuming green bean extractcan help accelerate the production an expenditure of breastmilk. This is because it containsvarious nutritional compositions, including protein, iron and vitamin B1. To improve exclusivebreastfeeding, an innovation is needed to help produce more breastmilk. Therefore, the writeris interested in applying giving green bean extract to postpartum mother for increasing theproduction and the acceleration of breastmilk. Objective: To find out the production andexpenditure of breastmilk of a postpartum mother after consuming green bean extract. Method:This paper is an analytical descriptive with a case study. Data was obtained from observationand literary study. The participants were 23 postpartum mothers who met the inclusivecriteria. The instruments used were observation sheet and the Procedure OperationalStandard. Result: After consuming green bean extract, there was a better increase inproduction and expenditure of breastmilk. Conclusion: Green bean extract can help increasethe production and expenditure of breastmilk of postpartum mothers.